Android smartphone: Battery saving service - Ismail, Zahid; Ali, Muna A.; Nassr, Rasheed (2011)
Saving power of Smartphone’s battery becomes an important because of appearance of applications and technologies that consume more power such as GPS and wifi. This paper reports on development and evaluation of an Android service to save power, it tries to utilizes Smartphone idle times to stop technologies such as Wifi and Bluetooth and application that may consume battery power; this service reads settings, configured by user, and stops/resumes technologies and application accordingly when events such as Screen goes off/on, wifi signal becomes weak or not exist, and when user goes to non-covered area. The idea behind this service is to increase battery life by stopping power-consuming while user does not use application and technologies. An empirical study has been conducted to evaluate the effectiveness of this service on Android Smartphone. The result shows there is a slight increase in battery life.